Uncooled р(Pb₁₋xSnxSe)-n(CdSe) heterostructure-based photodetector for the far infrared spectral range - Lepikh, Ya.I.; Ivanchenko, I.A.; Budiyanskaya, L.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The possibility to create uncooled photodetector (PD) in the region close to
l = 10 μm being based on p(Pb₁₋xSnxSe)-n(CdSe) heterojunction has been conceptually
and practically confirmed. Design and technology of uncooled thin-film PD based on
Pb Sn Se₁₋x p -n(CdSe) heterojunction in which broad-band CdSe layer is located on
the illuminated surface and plays the role of the optical filter with respect to the lower
layer of ternary compound. The PD spectral characteristics at room temperature have
been researched, which confirms the photoactivity of both heterojunction layers. The
mechanism of current flow in the PD structure based on the above heterojunction and
the mechanism of the PD samples sensitivity at room temperature in the far infrared
spectrum, the determining factor of which is the amount of wide-gap semiconductors
where space charge-limited current appears, have been investigated. The uncooled PD
detectability typical for polycrystalline structures 106
…107 сm*Hz¹/²/W has been
discovered.